Comparative data of single versus double proglide vascular preclose technique after percutaneous transfemoral transcatheter aortic valve implantation from the optimized catheter valvular intervention (OCEAN‐TAVI) japanese multicenter registry. Issue 3 (27th October 2016) - Kodama, Atsuko; Yamamoto, Masanori; Shimura, Tetsuro; Kagase, Ai; Koyama, Yutaka; Tada, Norio; Takagi, Kensuke; Araki, Motoharu; Yamanaka, Futoshi; Shirai, Shinichi; Watanabe, Yusuke; Hayashida, Kentaro
Abstract : Objectives: This study aimed to assess the feasibility of percutaneous arterial access site closure after percutaneous transfemoral transcatheter aortic valve implantation (TF‐TAVI) using single versus double Perclose ProGlide devices. Backgrounds: Although suturing with the preclose technique has been widely adopted during TF‐TAVI, the optimal vascular closure strategy is still under debate. Methods: Data from 279 patients who underwent TF‐TAVI, obtained from the Optimized CathEter vAlvular iNtervention (OCEAN‐TAVI) Japanese multicenter registry. Technical, procedural, and clinical outcomes were compared between the single ProGlide group ( n  = 99) and double ProGlide group ( n  = 180). They were also analyzed by propensity adjusted matching model (single [ n  = 69] vs. double [ n  = 69]). All patients were treated through a 16‐Fr to 20‐Fr eSheath. Technical success of the closure device was defined as hemostasis not requiring alternative invasive treatment. Access site‐related vascular complications, bleedings, and other procedural complications were defined according to the Valvular Academic Research Consortium‐2 (VARC‐2) criteria. Results: The rates of technical success and access site‐related vascular complications were similar in the 2 groups (94.9% vs. 91.6%, p  = 0.44; 5.0% vs. 7.7%, p  = 0.54, respectively). The prevalence of bleeding complications did not differ between the 2 groups (1.0% vs. 3.3%, p  = 0.43). Thirty‐day mortality rate also showed no difference between the 2 groups (2.0% vs. 1.1%, p  = 0.95), although these events were not associated with access site failure. These results were not attenuated in the propensity matching model. Conclusions: Vascular closure with a single ProGlide in TF‐TAVI could achieve equivalent, acceptable rates of technical success and procedural complications compared with the double ProGlide technique. © 2016 Wiley Periodicals, Inc.